Wireless Bioelectronics Towards Treatment of Glioblastoma Multiforme. (12th October 2019) - Shaw, Andie; Sanjuan-Alberte, Paola; Hague, Richard; Rahman, Ruman; Rawson, Frankie
Abstract: 'Bioelectronic therapies' are defined as treatments that provide therapy via electrical stimulation. As electrochemical signalling is a key communication pathway of the human body, learning and modulating these signals could allow us to regenerate lost functions and restore health where previously regarded impossible. Bioelectronics do not yet fully exploit this possibility as they lack resolution and plasticity to fully merge with biology. We aim to negate these problems by pioneering the development of wireless bioelectronics. One exciting area we hope this can be applied is that of tumour treating fields (TTFs). TTFs apply electric fields to a tumour region, providing a non-invasive anti-mitotic treatment modality. This anti-mitotic behaviour arises due to dipole alignment and di-electrophoresis. However, an understanding of the exact mode of action has not yet been reached. We aim to improve this knowledge by analysing how healthy astrocytes vs glioblastoma cells behave in various electrical systems: comparing ionic currents with electric fields. Furthermore, we hope to improve targeting of TTFs through the in-situ growth of conductive structures, via wireless electrochemistry. Proof of concept has been achieved by wirelessly growing silver micro-wires in the presence of U251 glioblastoma cells. Wire growth has been optimised without the presence of cells, allowing controlled growth direction via electrode geometry. Wires range from 2–9µm in diameter and have been shown to be conductive through the completion of a circuit lighting an LED. Such structures could ultimately be grown in the region of a tumour, therefore therapeutically targeting the electric field to that site.